2 STUDI PENGOLAHAN MAKANAN DI KANTIN FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - Bahrudi, Bahrudi; Elida, Elida; Kasmita, Kasmita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
The purpose of this study is to describe the process of preparation, processing and presentation processes of foodstuffs in the canteen of Faculty of Engineering University of Padang. The type of this research is using descriptive qualitative approach. The technique of data retrieval is done by interview or observation guidelines in the form of questions and documentation. The data source or informant in this research is the owner of the canteen and the employees of cafetaria in Faculty of Engineering, The University of Padang. The data analyses are used data reduction, data display / data presentation, and verification. The results showed that (1) the preparation tool in the cafeteria of Faculty of Engineering is not complete yet. The process of preparation the materials are quite good, just in the process of cutting the side dishes are not done in the canteen of the Faculty of Engineering. In the process of preparing vegetables carried out after the cutting process, so it can reduce the nutritional value. (2) The processing procedure of the vegetables seems the employee of the cafeteria make it over cook. Beside that, the additional of MSG does not use the measuring instrument. 3. The Presentation techniques are done by organized the food by using Pyrex, and laid it out on the counter.Keywords: Food Processing, Diner, Faculty of Engineering.